PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PTPS GOMBENGSARI DI BANYUWANGI - Hovivah, Windi; Kusnadi, Edy; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
Human resource management is the science and art of regulating the relationship and role of the workforce to be effective and efficient in helping the realization of the goals of the company, employees, and society. Human resource management focuses on the problem of human labor which is arranged according to its functions, to be more effective and efficient in realizing the goals of the company, employees, and society. The purpose of this study was to analyze and examine the influence of organizational culture in determining employee performance with motivation as an intervening variable. The population in this study are employees of PTPS Gombengsari in Banyuwangi. The sampling method was determined with a saturated sample. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that organizational culture has a significant positive effect on motivation, organizational culture has a significant positive effect on employee performance, motivation has a significant positive effect on employee performance. The results of the indirect influence hypothesis show that the organizational culture variable on employee performance through motivation has a significant positive effect.